Mass-spectrometric studies of the charge for CdWO₄ crystal growth - Sofronov, D.S.; Nagornaya, L.L.; Tupitsyna, I.A.; Kudin, K.A. (Functional Materials, 2009)
The cadmium tungstate charge has been tested by mass-spectrometry. The charge criterion quality is the absence of ammonia-containing impurities that form ammonia and hydroxide under decomposition. The preliminary heat treatment in air at 700°C favors the removal of organic impurities, ammonium salts, and hydroxides. Проведено тестування шихти вольфрамату кадмію мас-спектрометричним методом. Критерієм якості шихти є відсутність домішок амонієвих сполук, які розкладаються з утворенням аміаку та гідроксидів. Попередня термічна обробка шихти в атмосфері повітря при температурі 700°С сприяє видаленню органічних домішок, амонієвих сполук та гідроксидів. Проведено тестирование шихты вольфрамата кадмия масс-спектрометрическим методом. Критерием качества шихты является отсутствие аммониевых примесей, разлагающихся с образованием аммиака и гидроксидов. Предварительная термическая обработка шихты в атмосфере воздуха при температуре 700°С способствует удалению органических примесей, аммониевых солей и гидроксидов.